Chicanas of 18th Street: Narratives of a Movement from Latino Chicago. - Kirkpatrick, David C. (Fides et historia, 2012)
The article reviews the book ''Chicanas of 18th Street: Narratives of a Movement from Latino Chicago,'' by Leonard G. Ramírez.